SAT0273 PROGNOSTIC FACTORS FOR POOR OUTCOME IN BEHÇET'S SYNDROME WITH NEUROLOGICAL INVOLVEMENT: RESULTS FROM A CLINICAL LONG-TERM FOLLOW-UP OF A SINGLE CENTRE. (2nd June 2020) - Sahin Eroglu, D.; Torgutalp, M.; Sezer, S.; Boyvat, A.; Yucesan, C.; Ates, A.
Abstract : Background: Behçet's Syndrome (BS) is a vasculitis of unknown cause. Neurological disease is a type of its serious involvement and causes morbidity and mortality. Objectives: In this study, we aimed to describe the clinical characteristics of neuro-Behçet Syndrome (NBS) and to define prognostic factors that were associated with poor outcome. Methods: Among 2033 patients with BS, we performed a retrospective analysis of 94 patients (52.1% male; mean age 36.1 (11.9) years), who fulfilled the ISG-1990 for BS. We divided patients into two subgroups, either parenchymal (p-NBS) or non-parenchymal (np-NBS). Clinical, laboratory, and imaging characteristics of the patients were defined. We described the poor outcome as a modified Rankin score (mRS) >= 3 at last follow-up and/or death, and assessed the predictor factors associated such kind of outcome. Results: In total, 52 (55.3%) patients presented with p-NBS, of whom 15 (28.8%) had progressive course, and 42 (44.7%) presented with np-NBS (Table.1). Ocular involvement was more common in p-NBS than np-NBS (59.6% vs. 39.1% respectively, p=0.04), whereas vascular involvement excluding sinus vein thrombosis was more frequent in patients with np-NBS (15.4% vs. 50.0%, respectively, p=0.001). Headache and papilledema were frequently observed in np-NBS (p<0.001), whereas paresis, sensory symptoms, pyramidal and cerebellar signs were significantly common in p-NB (<0.001). Twenty-five patients (26.6%) experienced at least one relapse. After a median of 54 (IQR 79.4) months, 11 patients (11.7%) had disabling sequela and a total of 5 (5.3%) deaths occurred. Characteristics of patients with and without poor outcome are presented in table 2. In multivariable logistic regression analysis, factors associated with poor outcome were initial mRS (OR 24.2 (95% CI 3.16 – 108.67)) and age >= 40 at NBS diagnosis (OR 4.59 (95% CI 1.02 – 20.69)), meanwhile, headache at presentation was associated with a lower risk for poor outcome. (OR 0.22 (95% CI 0.05 – 0.91)). Conclusion: Neurologic involvement is a detrimental manifestation of BS and causes disability, even death. Patients who have an initial disabling presentation in advanced age are more likely to have poor prognosis. Treatment intensification in this subpopulation might be considered. References: None Disclosure of Interests: None declared